2019
DOI: 10.1155/2019/5268031
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Antiproliferative Effect of Ankaferd Hemostat on Caco-2 Colon Cancer Cells via LC/MS Shotgun Proteomics Approach

Abstract: Ankaferd hemostat (ABS), a traditional herbal extract, is a hemostatic agent used for wound healing and bleeding treatment. A standardized form of plants contains many biomolecules. In recent years, previous studies have demonstrated the antineoplastic effect of ABS. In the present work, we focused on the mechanism of its antineoplastic effect over Caco-2 colon cancer cells. The LC/MS-based proteomics method was used to understand the effect of ABS at the protein level. The results were evaluated with gene ont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 71 publications
0
8
0
Order By: Relevance
“…A previous study showed that DHA can play a protective role in initiation and development of colitis-associated CRC ( 19 ). Moreover, endoscopic topical drugs Ankaferd hemostat also shows the anti-CRC effect, which suppresses the proliferation of CRC cells by regulating its cell metabolism and cell cycle ( 33 ). In addition, previous studies demonstrated that other antimalarial drugs also suppress the malignancy of CRC.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study showed that DHA can play a protective role in initiation and development of colitis-associated CRC ( 19 ). Moreover, endoscopic topical drugs Ankaferd hemostat also shows the anti-CRC effect, which suppresses the proliferation of CRC cells by regulating its cell metabolism and cell cycle ( 33 ). In addition, previous studies demonstrated that other antimalarial drugs also suppress the malignancy of CRC.…”
Section: Discussionmentioning
confidence: 99%
“…ABS has effects on colon cancer cells. The mechanism of antineoplastic effect of ABS over the Caco-2 colon cancer cells has been evaluated (Figures 2 and 3 ) [ 10 ]. ABS found to change glucose, fatty acids, and protein metabolisms.…”
Section: Molecular Basis Of Antineoplastic Roles Of Ankaferd Hemostat...mentioning
confidence: 99%
“…After reduction, the proteins were incubated with 100 mM iodoacetamide (Sigma) at room temperature in the dark. The proteins were digested by trypsin (Sigma, 1:100, w/w) at 37 C for 16 h. After the desalting process, the tryptic peptides were dissolved in acetonitrile containing 0.1% formic acid (Kocak & Altinoz, 2020;Kocak et al, 2019).…”
Section: Proteomics Analysismentioning
confidence: 99%